Geology and Land Suitability Analysis for Final Processing Waste Site in Ambon Island - Mailoa, Winardcova Vania Cerwyn; Kololu, Micky; Ulfa, Yuniarti; Puradimadja, Deni Juanda (BRIN Publishing, 2024)
The production of waste in Ambon City increased from 200 tons per day to 297 tons per day between 2017 and 2021, yet the state of the Toisapu landfill in Ambon did not keep up with this growth. The Toisapu landfill has been in operation since 2007, however, due to its proximity to residential areas and slope of more than 20 percent, it is currently in an overload state and requires a re-evaluation. The goal of this study is to identify a different landfill to replace the Toisapu landfill that fulfills the Indonesian National Standards and functions as a Waste Processing and Final Processing Site (TPPAS). This study combines an evaluation of the geological and non-geological parameters using an environmental geological technique called Spatial Multi-Criteria Evaluation (SMCE). In order to determine the most possible land, the study findings for each parameter are superimposed, assigned a value, and then added together. According to the research's findings, Wakal, which has 126,668 hectares of land is the best option. Since the groundwater in this area is quite deep (>80 meters) and has low permeability, there is minimal possibility of leachate seepage contaminating the groundwater. Wakal, unlike the Toisapu landfill, is located far from inhabited areas and protected forests, with a slope of less than 20%.